Makna al-Dhalalah dalam Al-Qur`an - Furqan Amri; Samsul Bahri; Ahmad Suryani (TAFSE: Journal of Qur'anic Studies, 2019)
There are two groups of verses in the Qur'an that have gaps in attributing al-dhalalah to Allah. The first group of verses attributes al-dhalalah to come from Allah, not a direct result of the servant's actions. Another group of verses attributes al-dhalalah to come from the servant, not from Allah. In this paper, the author examines the meaning of al-dhalalah expressed in the Qur'an with the aim of explaining the meaning of al-dhalalah contained in the verses of the Qur'an. This study is a literature study with descriptive analysis through the maudhū'i interpretation method. The word dhalla in its various forms is not less than 190 times repeated in the Qur'an. In order to eliminate the contradictory meanings of the two groups of contradicting verses, it must be understood in a syar'i way, not only understood textually (mantuq). The existence of this contradiction indicates that the meaning to be shown by the two groups of verses is the syar'i meaning, not the textual meaning (mantūq). So it can be concluded that understanding the two groups of verses of al-dhalalah it cannot only be understood textually but must be understood with a syar'i approach, by looking at the qarīnah point of view contained in each verse. The ratio of al-dhalalah to Allah SWT is only a ratio of creation, not a direct ratio, while the direct subject of al-dhalalah is humans. Ada dua kelompok ayat dalam al-Qur’an yang memiliki kesenjangan dalam menisbahkan al-dhalalah kepada Allah Swt. Kelompok ayat pertama menisbahkan al-dhalalah datang dari Allah, bukan akibat langsung dari perbuatan hamba. Kelompok ayat lain menisbahkan al-dhalalah datang dari hamba bukan dari Allah Swt. Dalam tulisan ini, penulis mengkaji makna al-dhalalah yang diungkapkan dalam al-Qur’an dengan tujuan untuk menjelaskan makna al-dhalalah yang terkandung dalam ayat-ayat al-Qur’an. Kajian ini merupakan studi kepustakaan dengan analisis deskriptif melalui metode tafsir maudhū’i. Kata dhalla dalam berbagai bentuknya tidak kurang dari 190 kali terulang dalam al-Qur’an. Untuk meniadakan kontradiksi makna dari dua kelompok ayat yang bertentangan, harus dipahami secara syar’i tidak hanya dipahami secara tekstual (mantuq). Adanya kontradiksi ini menunjukkan bahwa makna yang hendak diperlihatkan oleh kedua kelompok ayat adalah makna syar’i bukan makna tekstual (mantūq). Sehingga dapat disimpulkan, bahwa dalam memahami dua kelompok ayat al-dhalalah tidak bisa hanya dipahami secara tekstual, akan tetapi harus dipahami dengan pendekatan syar’i, dengan melihat dari sudut pandang qarīnah yang terkandung dalam setiap ayat. Nisbah al-dhalalah kepada Allah Swt hanya sekedar nisbah penciptaan bukan nisbah secara langsung, sedangkan subyek langsung dari al-dhalalah adalah manusia.